Memanfaatkan Kekayaan Lokal Untuk Meningkatkan Keterampilan Prakarya dan Kewirausahaan Melalui Model Project Based Learning (PjBL) di SMA Muhammadiyah Sokaraja - Rusmiyati; Kertopati, Beny Wijarnako (UM Purwokerto Press, 2024)
Craft and Entrepreneurship Learning (PKWU) is a subject that focuses on creating work and entrepreneurial activities. To understand the material about the processing of Sokaraja fried getuk food which is based on the use of local wealth, the Project Based Learning (PjBL) method is very necessary. This learning model is used because it involves student activities in the learning process, which aims to solve problems so as to help them understand the subject matter better. This research uses a descriptive qualitative approach that reveals an in-depth picture of students' creativity. Researchers focus on exploring products and ideas produced by students as a real manifestation of their creativity.